(untitled) (Tamaddun, 2024)
This study examines students’ perceptions of Google Classroom as a tool for English reading instruction, utilizing Davis’ (1989) Technology Acceptance Model to explore the interplay of perceived usefulness and ease of use in shaping their experiences. Employing a qualitative research design, data were collected through semi-structured interviews with five second-semester English education students selected through purposive sampling. Thematic analysis revealed both positive and negative perceptions of the platform. Positive perceptions centered on its accessibility, usefulness, efficiency, flexibility, and user-friendly features, which supported students in organizing tasks, managing time, and accessing learning materials seamlessly. However, challenges included dependence on stable internet connections and limited interactivity, which hindered collaborative learning and engagement. These findings underscore the dual nature of Google Classroom as both a facilitator and a constraint in digital learning environments. The study highlights the need for improved infrastructure, professional development for educators, and integration of supplementary tools to address identified limitations. The results contribute to the growing body of literature on technology-enhanced learning and offer practical implications for optimizing the use of digital tools in English as a Foreign Language (EFL) education. Future research should explore blended learning models and the integration of interactive tools to enhance the effectiveness of LMS platforms in fostering active and equitable learning experiences.